INCREASING SKILLS OF WRITING DESCRIPTIVE TEXT THROUGH SYNTHETIC ANALYTIC METHOD - Lily Andria; Teti Sobari (JLER (Journal of Language Education Research), 2018)
Abstract The purpose of this study is to know if the skills of writing descriptive text using synthetic analytic method is better than using the usual method. Writing skills are harder to master. Though it is important for students to master writing skills. In the Indonesian Language curriculum, writing skills are taught especially in junior high school (SMP). Teachers are encouraged to pay more attention to teaching the structure of the descriptive text in developing ideas, setting ideas, and vocabulary. From these problems the writer offers the use of Synthetic Analytic approach to improve students' understanding in learning Indonesian language in junior high.  However, in reality learning writing in schools still face a lot of obstacles and tend to be avoided. This study used quasi-experimental method. The population in this study is one of the students of SMP Negeri in Bandung and the subject of the research sample 2 classes of class VII.  Based on the results of research and discussion obtained Sig value. 0.001 because the value of Sig < 0.05 then H0 rejected means the improvement of students' text writing skills using synthetic analytic methods is better than those who get the usual method of learning used by teachers. Keywords: Writing skills, Synthetic Analytical Method